2021
DOI: 10.4103/njcp.njcp_266_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drug-drug Interactions in Cancer Patients Treated at a University Hospital in North Cyprus Using Two Interaction Databases

Abstract: Background: Drug interactions in oncology are of clinical importance owing to the inherent use of multiple medications in cancer treatment which predisposes patients to drug-related problems. Aim: This study aimed to compare two electronic databases based on the frequency, mechanism and severity of drug-drug interactions (DDIs) in cancer treatment at Near East University Hospital. Method: A retrospective obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…This study found that nearly half of the mechanisms of PDDIs identified by Drugs.com and Lexicomp Drug Interactions were pharmacokinetic interactions. This finding is consistent with another study in which 50% of interactions were pharmacokinetics,26 43 but opposes a study conducted in Sudan in which the majority of drug interactions were pharmacodynamic interactions 24. This difference may be due to different therapeutic regimens used in different hospitals 50.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This study found that nearly half of the mechanisms of PDDIs identified by Drugs.com and Lexicomp Drug Interactions were pharmacokinetic interactions. This finding is consistent with another study in which 50% of interactions were pharmacokinetics,26 43 but opposes a study conducted in Sudan in which the majority of drug interactions were pharmacodynamic interactions 24. This difference may be due to different therapeutic regimens used in different hospitals 50.…”
Section: Discussionsupporting
confidence: 89%
“…However, studies also reported that major DDIs were frequently identified 39 48. This difference might be due to the use of different drug interaction screening databases, which have different sensitivities,26 49 and the use of different therapeutic regimens in different hospitals 50. The most frequent drug interactions identified by Medscape were significant drug interactions followed by minor interactions, which is in line with a previous study 11 28 41 45.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations